Which one of the types of programmed cell death is reduced by aerobic exercise? - Peyman Akraminia; Rezvan KheirAndish; Negin Kordi; Ali Saydi (Journal of Exercise & Organ Cross Talk)
Programmed cell death is a critical element of the body’s defense system. Exercise represents a physiological stressor that triggers an adaptive response within the body. It has been suggested that various forms of programmed cell death are essential for the adaptation process associated with exercise. During physical activity, mechanisms such as apoptosis and autophagy are activated to mitigate tissue damage, restore cellular integrity, resolve inflammatory responses, and facilitate direct signals that promote adaptation. The induction of programmed cell death is mediated by specific factors, including reactive oxygen species, cytokines, and hormones. These cell death pathways are initiated by the presence of altered proteins and organelles, with the objective of conserving and recycling cellular resources. In scenarios where cells accumulate damaged molecules and repair mechanisms become overwhelmed, programmed cell death is triggered. In this review article, we have examined the types of programmed death and the effect of aerobic training on these deaths.